The Influence of Financial Slack and Gender Board Diversity on The Quality of Sustainability Report Disclosure With Board of Commissioners' Effectiveness as A Moderating Variable - Ni Luh Apriani; Lucy Sri Musmini; Desak Nyoman Sri Werastuti (Eduvest - Journal of Universal Studies, 2025)
This study aims to examine the effect of financial slack, board diversity gender on the quality of disclosure of sustainability reports with the effectiveness of the board of commissioners. The population used in this study is banking companies listed on the Indonesia Stock Exchange (BEI) in 2019 - 2023. The sample used is based on predetermined criteria. The analysis technique used is descriptive analysis, SEM PLS and hypothesis testing using the Smart PLS 4.0 program. This study shows the results that: (1) Financial slack has no effect on the quality of disclosure of sustainability reports in the banking industry. (2) Board diversity gender has a significant positive effect on the quality of disclosure of sustainability reports in the banking industry. (3) The effectiveness of the board of commissioners has a significant positive effect on the quality of disclosure of sustainability reports in the banking industry. (4) The effectiveness of the board of commissioners is unable to moderate the relationship between financial slack and the quality of disclosure of sustainability reports in the banking industry. (5) The effectiveness of the board of commissioners is unable to moderate the board diversity gender relationship on the quality of disclosure of sustainability reports in the banking industry.